2020
DOI: 10.3892/etm.2020.9253
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑142 protects MC3T3‑E1 cells against high glucose‑induced apoptosis by targeting β‑catenin

Abstract: Osteoporosis, characterized by decreased mineral density and bone mass, is triggered by various detrimental factors and often causes further complications, including fractures. Aberrant expression of microRNAs (miRs) has been associated with the pathogenesis of osteoporosis. Recently, miR-142 was reported to be downregulated in osteoblasts; however, the underlying mechanism of miR-142 in mediating the development of osteoporosis remains unclear. In the present study, high glucose induced the downregulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…MC3T3-E1 cells were purchased and cultured as in a previous study [ 7 ]. Briefly, cells were cultured in α-MEM under standard conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC3T3-E1 cells were purchased and cultured as in a previous study [ 7 ]. Briefly, cells were cultured in α-MEM under standard conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis and progression of OP might be affected by aging, genetic factors, bad living habits, and nutritional deficiency, among which, the imbalance of bone homeostasis is one of the key factors [ 3 , 4 ]. There is increasing evidence that lipid metabolism disorders, such as atherosclerosis (AS) and OP, share common underlying pathogenesis involving bone and vascular mineralization, as well as age-related degenerative processes [ 5 , 6 , 7 ]. However, the specific mechanism of action between lipid and bone metabolism disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…72 Controversially, Zheng et al reported that miR-142 has a protective effect on osteoblasts in a high-glucose environment. 73 They showed that miR-142 can block the Wnt signaling pathway by targeting β-catenin to suppress the onset of high glucose-induced apoptosis. Another debated one is miR-146a, which was reported to be engaged in both promoting and inhibiting osteoblastic apoptosis.…”
Section: Mirnas In Regulating Osteoblast Apoptosismentioning
confidence: 99%
“…Recently, there has been growing interest in exploring the function of miRNAs in HG‐induced osteoblasts (B. Liu et al, 2012). For example, miRNA‐142 can protect MC3T3‐E1 cells against HG‐induced apoptosis by targeting β‐catenin (Zheng et al, 2020), miRNA‐590‐5p can antagonize the inhibitory effect of HG by suppressing Smad7 (Chen et al, 2019). Emerging evidence suggested that miRNA‐144 participates in osteoblasts' differentiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%